Unemployment and econometric learning. Issue 2 (June 2018) - Schaefer, Daniel; Singleton, Carl
Highlights: We relax rational expectations in the textbook model of a frictional labour market. "Good econometrician" agents can learn the rational expectations equilibrium. Simulations of the model show that learning and convergence is slow. Learning is not a workable solution to the 'unemployment volatility puzzle'. Abstract: We apply well-known results of the econometric learning literature to the Mortensen and Pissarides real business cycle model. Agents can always learn the unique rational expectations equilibrium (REE), for all possible well-defined sets of parameter values, by using the minimum-state-variable solution to the model and decreasing gain learning. From this perspective the assumption of rational expectations in the model could be seen as reasonable. But using a parametrisation with UK data, simulations show that the speed of convergence to the REE is slow. This type of learning dampens the cyclical response of unemployment to small structural shocks.